Meretas Jalan Menuju Kota Impian:Kolaborasi Masyarakat Dalam Pembangunan Berkelanjutan - MA Syaripudin; Siregar, Serlita Cindana; M. Rayendra; Saputri, Elsa; Maya Sari, Sheila; Khaula Nuria, Yolanda; Tiyas, Sewining; Melinda, Shantica (STMIK Royal, 2026)
Abstract: This article examines community service initiatives conducted through the Integrated Student Community Service (KKN-Terintegrasi) program at UIN Raden Intan Lampung. This program was implemented at the request of the Mayor of Bandar Lampung, who specifically sought optimal solutions for various local issues, including recurrent flooding within the city. Based on focus group discussions between Student Group 221 and local community stakeholders in flood-prone areas, a sustainable urban development model was formulated, emphasizing active collaboration among the government, academia, the private sector, and civil society. The methodology employed the Asset-Based Community Development (ABCD) framework with a participatory approach. The initiatives of Group 221 focused on three primary pillars: the circular economy, community-based environmental management, and the strengthening of social inclusion. The results demonstrate that collaborative initiatives are capable of producing innovative and sustainable solutions tailored to the needs of the city, while simultaneously fostering collective awareness regarding the importance of urban development oriented toward common welbeing. Keywords: community collaboration; dream city; and sustainable development. Abstrak: Artikel ini mengkaji kegiatan pengabdian masyarakat yang dilaksanakan melalui kegiatan KKN-Terintegrasi UIN Raden Intan Lampung. Kegiatan KKN-Terintegrasi dilaksanakan atas permintaan Wali Kota Bandar Lampung yang secara khusus meminta solusi terbaik atas beberapa permasalahan yang dihadapi termasuk musibah banjir yang terjadi secara berulang di Kota Bandar Lampung. Hasil diskusi kelompok 221 Mahasiswa UIN Raden Intan bersama potensi masyarakat di beberapa titik rawan, dirumuskan model pembangunan kota berkelanjutan melalui kolaborasi aktif antara pemerintah, akademisi, sektor swasta, dan masyarakat sipil. Metode diterapkan dengan pola ABCD (Assets Base Community Development), dengan pendekatan partisipatif. KKN-Terintegrasi kelompok 221 berfokus pada tiga pilar utama, yakni; perekonomian sirkular, pengelolaan lingkungan hidup berbasis komunitas, dan penguatan inklusi sosial. Hasil menunjukkan bahwa inisiatif kolaboratif mampu menghasilkan solusi inovatif dan berkelanjutan yang relevan dengan kebutuhan Kota Impian, serta dapat meningkatkan kesadaran kolektif terhadap pentingnya pembangunan kota yang berpihak pada kesejahteraan bersama. Kata Kunci: kolaborasi masyarakat; kota impian; dan pembangunan berkelanjutan.